PENGARUH INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN - Annisa Nadiyah Rahmani (LPPM UNIBI, 2019)
The purpose of this study is to determine the effect of intellectual capital on the firm’s value with the financial performance as intervening variabel in manufacturing firmsregistered in Indonesia Stock Exchange in period 2015-2017. This research examineintellectual capital in 2015 toward firm value with financial performance as interveningvariable in 2015, 2016 and 2017. This research wants to know the influence of intellectualcapital perceived in the same year, leg+1, or leg+2. Intellectual capital is measured usingPulic model. Firm’s value is measured using Tobin’s q model. The sample used in thisstudy are 114 manufacturing firms in Indonesia Stock Exchange in period 2015-2017.Multiple Liniar Regression used to be analysis technique using program SPSS 22. Theresult of this study show that intellectual capital has a positive effect on firm value in 2016and 2017.